Analysis of parent and F1 progeny verification in African yam bean (Sphenostylis stenocarpa Hochst, Ex. A. Rich. Harms) using cowpea SSR markers - Adefiranye, A.O.; Ogunkanmi, L.A.; Adeyemo, O.A.; Olatunde, T.E.S.; Paliwal, R.; Abberton, M.T.; Oyatomi, O.A. (MDPI, 2024)
African yam bean (Sphenostylis stenocarpa Hochst, Ex. A. Rich. Harms) is an important grain legume in Sub-Saharan Africa because of its nutritional value and adaptability to various agroecological zones. To foster the varietal development of improved African yam bean (AYB) genotypes with economic traits, it is necessary to validate parental polymorphism for key markers in selecting progenies from crosses between desired parents. This study aims to analyze the genetic fidelity between parents and F1 progenies in African yam bean through putative cowpea simple sequence repeat (SSR) markers. Hence, a total of seventy-seven progenies were derived from four sets of biparental crossings using drought-susceptible (TSs-96, TSs-363, and TSs-274) and drought-tolerant (TSs-417, TSs-111, and TSs-78) AYB accessions. These were validated using 120 cowpea primers targeting SSRs under optimal PCR conditions, and the size of the PCR-amplified DNA fragments was checked using gel electrophoresis. Twenty primers exhibited polymorphism in the parental lines, while ten displayed higher levels of the same polymorphism. The average polymorphism level for the surveyed SSR markers was 0.36. Given these findings, our study demonstrates that cowpea SSR markers are a reliable method for the regular testing and clear identification of AYB crosses, indicating potential AYB improvements.